2014
DOI: 10.1186/2049-2618-2-23
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the vaginal microbiota of healthy Canadian women through the menstrual cycle

Abstract: BackgroundThe vaginal microbial community plays a vital role in maintaining women’s health. Understanding the precise bacterial composition is challenging because of the diverse and difficult-to-culture nature of many bacterial constituents, necessitating culture-independent methodology. During a natural menstrual cycle, physiological changes could have an impact on bacterial growth, colonization, and community structure. The objective of this study was to assess the stability of the vaginal microbiome of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
161
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(182 citation statements)
references
References 64 publications
18
161
2
1
Order By: Relevance
“…Our findings are only inclusive of the 19 bacterial proteins confidently identified using our proteomics method; however, our results appear to be consistent with those of a pyrosequencing study examining the microbiota changes over the menstrual cycle of Canadian women. The study found the vaginal microbiome of most women to be relatively stable, and most women were predominantly colonized by Lactobacillus and Bifidobacterium species (58).…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are only inclusive of the 19 bacterial proteins confidently identified using our proteomics method; however, our results appear to be consistent with those of a pyrosequencing study examining the microbiota changes over the menstrual cycle of Canadian women. The study found the vaginal microbiome of most women to be relatively stable, and most women were predominantly colonized by Lactobacillus and Bifidobacterium species (58).…”
Section: Discussionmentioning
confidence: 93%
“…In nonpregnant women, longitudinal studies of the vaginal microbiota have demonstrated stability when viewed at a weekly timescale, punctuated by occasional daily fluctuations (25,(27)(28)(29)(30)(31)(32). These studies also documented significant variability among individuals with respect to the typical vaginal CST and its level of stability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of microbiota-host interactions have to control for menstrual cycle phase, which affects both cytokine levels (145,146) and microbial composition (147,148). Cervical ectopy (columnar epithelium replacing the squamous multilayer epithelium of the ectocervix), which is hormone dependent and especially common in adolescents, is also characterized by higher levels of proinflammatory mediators (146) and a shift to BV microbiota (149).…”
Section: Host Factors Associated With Vaginal Immune Functionmentioning
confidence: 99%